Application of Fullwaveform Tomography to VSP Walkaway Data. Issue 1 (1st December 2016) - Takougang, Eric Takam; Bouzidi, Youcef
Abstract : VSP walkaway data were collected in an oil field in the United Arab Emirates. 2D frequency domain fullwaveform tomography was used to obtain high resolution rock properties (P-wave), and structural information near and away from the borehole, following a specific data preconditioning and inversion strategy. The field data were inverted between 4 and 50 Hz, and the starting model was obtained from traveltime tomography. The results of the inversion show zones with anomalous low velocities that correlate in places with known presence of hydrocarbons, and highlight their possible extensions. A comparison of the results at the borehole location with the sonic log shows a generally good match. However, some mismatches are evident and can be explained by possible anisotropy and out of the plane structures not taken into account during the inversion.